The Differential Diagnosis of Bilateral Pleural Effusion and Multiple Mediastinal Lymphadenopathies Includes Kikuchi-Fujimoto Disease - Chienhsiu Huang MD (SAGE Publishing, 2020)
Kikuchi-Fujimoto disease is an uncommon lymphohistiocytic disorder that frequently presents with acute or subacute clinical disease course. Cervical lymphadenopathy is the most common involved lymph node. Very rare cases of pathologic diagnosis of Kikuchi-Fujimoto disease with bilateral pleural effusion and multiple mediastinal lymphadenopathies have been reported in the literature. In this article, we report the case of a 60-year-old male presented with bilateral pleural effusion and multiple mediastinal lymphadenopathies. He received video-assisted thoracoscopic surgery of the right pleura and thoracoscopic excision of the mediastinal lymph node. The pathologic findings from the lymph node and pleura were compatible with Kikuchi-Fujimoto disease. He was treated with oral hydroxychloroquine and oral prednisolone. A computed tomography scan of the chest 4 months later showed regressive mediastinal lymphadenopathy and bilateral pleural effusion. Our case is a first reported case of Kikuchi-Fujimoto disease diagnosis by the pathology of the lymph node and pleura in the literature. Results from our case suggest that Kikuchi-Fujimoto disease should be included in the differential diagnosis of bilateral pleural effusion and multiple mediastinal lymphadenopathies.